The Golden Rule and Sustainable Development - Zecha, Gerhard (Problemy Ekorozwoju, 2011)
Treat others as you want to be treated is one of the most familiar formulations of the Golden Rule. In this article, seven different expressions are described that can all be seen as varieties of the same rule. The Golden Rule can be a very useful instrument for Applied Ethics in both theoretical and practical moral thinking. However, none of these variations gives a definite moral advice. The reason is that the Golden Rule does not contain any reference to value standards. It rather serves as a rule of reversibility and consistency that tells us that we should act upon others as we would like to be treated by them, i.e. the Golden Rule asks for a harmony between our moral actions and our desires. This Principle of Reciprocity may lead to a number of misconceptions, but several examples serve to gain a morally acceptable understanding of this universal moral code.